Location based Augmented Reality – GeoAR - Suriya, S; R, Saran kirthic (Journal of ISMAC, 2023)
This study aims to research on immersive and interactive experience to users by using augmented reality and GPS technology. The system will be built using the Vuforia engine or ARcore support, and will be able to detect the user's location and device location using GPS. Once the system is initiated, it will check for GPS support in the user's device and ask for camera access. Then, using Vuforia's markerless tool and AR+GPS package, the system will detect the user's location and search for the rendered scene for the respective location. Each building will be labelled with AR objects for better understanding of the place and tracking where the user is. The AR objects will provide information about the building, such as its name, purpose, and history. This will enhance the user's experience and enable them to navigate the campus more easily. The application will create a scene that renders the real environment image and the rendered AR scene image, providing an interactive output. Users will be able to interact with the AR objects by clicking on them to access more information, such as photos and videos. Overall, the proposed system will be a useful tool for navigating the campus, providing users with a unique and immersive experience.
Keywords: Augmented Reality; AR core; Vuforia; GeoAR; Location-based AR